Analysis of Social Media Marketing and Content Marketing on Purchase Decisions on MSMEs Fostered by Cinta Ayah Bunda Foundation Bandung - Susilawati*, Erna; Wulantika, Lita (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
The objective of this research is to determine whether there is an influence of Social Media and Content Marketing implemented in MSMEs under the guidance of Yayasan Cinta Ayah Bunda (YCAB) in Bandung on consumer purchasing decisions. The study involved 100 consumers from MSMEs under YCAB as samples, with data collected through questionnaire distribution via Google Form. The research methodology employed a descriptive-verification quantitative approach with multiple linear regression. The findings reveal partial effects of social media marketing and content marketing on purchasing decisions. Simultaneously, both social media marketing and content marketing have a positive and significant impact on purchasing decisions in YCAB-supported MSMEs in Bandung. Keywords: Social Media Marketing; Content Marketing; Purchasing Decision; MSMEs; Digital Marketing